2012
DOI: 10.1590/s0004-28032012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of adult-type hypolactasia/lactase persistence: genotyping of single nucleotide polymorphism (SNP C/T-13910) is not consistent with breath test in Colombian Caribbean population

Abstract: -Context -Genotyping of single nucleotide polymorphism (SNP C/T -13910 ) located upstream of the lactase gene is used to determine adult-type hypolactasia/lactase persistence in North-European Caucasian subjects. The applicability of this polymorphism has been studied by comparing it with the standard diagnostic methods in different populations. Objective -To compare the lactose hydrogen breath test with the genetic test in a sample of the Colombian Caribbean population. Methods -Lactose hydrogen breath test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This polymorphism is closely related with LP in the Finnish population, where it was first determined, and in the German, English, Italian, and even Indian populations [ 19 20 21 ]. However, no relationship could be found between lactase deficiency and the 13910 CT polymorphism in non-White populations such as Africans, the Chinese, and the Japanese [ 21 22 23 24 25 ]. The relationship between lactase deficiency and the 13910 CT polymorphism in the Turkish population is not known.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism is closely related with LP in the Finnish population, where it was first determined, and in the German, English, Italian, and even Indian populations [ 19 20 21 ]. However, no relationship could be found between lactase deficiency and the 13910 CT polymorphism in non-White populations such as Africans, the Chinese, and the Japanese [ 21 22 23 24 25 ]. The relationship between lactase deficiency and the 13910 CT polymorphism in the Turkish population is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to assess SNPs' associations with breath test and lactose tolerance test results 25 ,. The present study is the first study to evaluate correlations between different cutoffs for glucose levels in biochemical blood tests for lactose tolerance and genotyping of the SNPs C>T -13910 and G>A -22018 upstream of the lactase gene.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, diverse studies carried out in Brazil, Ecuador, Colombia, Peru, and Chile found the C/T‐13910 SNP to be the most frequent polymorphism associated with LP. However, T‐13910 allele frequency varies greatly depending on ethnic affiliation or genetic ancestry background of the population or individuals studied, being higher when European contribution increases (Fernández & Flores, 2014; Friedrich, Santos, et al, 2012; Guimarães Alves et al, 2021; Mattar et al, 2009; Mendoza Torres et al, 2012; Paz y Miño et al, 2016). Association between expected lactose digestion phenotype considering C/T‐13910 genotype, and the effectively observed phenotype, was assessed in some studies in South America.…”
Section: Introductionmentioning
confidence: 99%
“…Association between expected lactose digestion phenotype considering C/T‐13910 genotype, and the effectively observed phenotype, was assessed in some studies in South America. Authors reported statistical association of phenotype, determined with lactose tolerance test (LTT) or hydrogen breath test (H 2 BT), with expected phenotype in Colombian Caribbean and Ecuadorian populations, although with a modest agreement between them (Mendoza Torres et al, 2012; Paz y Miño et al, 2016). On the other hand, Montalvá et al (2019) found a strong association of genotype C/T‐13910 with lactose digestion phenotype, determined with LTT, in goat herders of central Chile.…”
Section: Introductionmentioning
confidence: 99%